The dramaturgic practice in dance: documental process in the Hot One Hundred Choreographers by Cristian Duarte (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Dramaturgical practice in dance can be perceived as a form of action and thought, occurring in a tense and processual manner, according to each composition. Due to the diversity of processes and choices within this realm, this article analyzed the dramaturgical construction of Brazilian choreographer Cristian Duarte in his choreographic production, which operates with a documentary process within the field itself: The Hot One Hundred Choreographers. The research was a case study that related to reference materials and semi-structured interviews. The artist's list was highlighted as a dramaturgical tool, emphasizing the value of Cristian's corpar in friction with the choreographers on the list, his choices for the scene, without a fixed structure, valuing equity and collectivity, along with the pursuit of his affections, creation of maneuvers, anchors, and a website. The piece prompts important discussions about contemporaneity, valuing our references and memories in their immanence, like the quasi-bodies that we are.
Keywords: dance; dramaturgy; references; choreographers; Cristian Duarte